An improved dispersion relation for parallel propagating electromagnetic waves in warm plasmas: Application to electron scattering. Issue 5 (23rd May 2013) - Chen, Lunjin; Thorne, Richard M.; Shprits, Yuri; Ni, Binbin
Abstract: [1] An improved dispersion relation, with thermal corrections retained, for parallel propagating electromagnetic waves in a warm plasma is developed for both left‒hand (L‒) and right‒hand (R‒) polarized modes. Compared with the cold plasma dispersion relation, the derived dispersion relation is in much better agreement with the full hot plasma dispersion relation (including the wave growth rate). The pitch angle scattering rates of energetic electrons are compared between using cold and full dispersion relation. Significant differences are found when evaluating pitch angle scattering rate of MeV electron caused by He + band waves in multiple ion plasmas. Due to He + ion cyclotron absorption, the He + band electromagnetic ion cyclotron waves, which are able to resonate with MeV electrons (at large wave number), tend to be strongly suppressed. Less significant differences in scattering rate of electrons between using cold and hot dispersion relation are found in the case of L‒mode waves in single H + ion plasma and in the case of R‒mode waves. Key Points: A warm dispersion relation for parallel propagating waves is derived Electron scattering rates by He+ band needs consideration of thermal effect Electron scattering rates by R-mode are similar with and without thermal effect